Corneal Properties in Primary Open-angle Glaucoma Assessed Through Scheimpflug Corneal Topography and Densitometry. Issue 5 (May 2021) - Molero-Senosiain, Mercedes; Morales-Fernandez, Laura; Saenz-Frances, Federico; Perucho-Gonzalez, Lucia; García-Bella, Javier; Garcia Feijoo, Julian; Martinez-de-la-Casa, Jose M.
Abstract : Purpose: The purpose of this study was to compare corneal topography and densitometry measurements in patients with primary open-angle glaucoma (POAG) and healthy subjects. Patients and Methods: A total of 200 eyes of 75 patients with POAG and 125 healthy controls underwent corneal topography and densitometry (Oculus Pentacam HR). The data compared in the 2 groups were: anterior chamber angle, anterior chamber depth, and anterior chamber volume, keratometry ( K minimum, K maximum, and K mean ), central corneal thickness, central anterior elevation, anterior elevation apex, maximum anterior elevation, and posterior elevation apex. Densitometry measurements were made at 3 depths on a 12-mm-diameter circle divided into 4 concentric rings (0 to 2, 2 to 6, 6 to 10, and 10 to 12 mm). The diagnostic capacity of the corneal variables was assessed through the areas under the receiver operating characteristics curve. Results: The corneal density of practically all depth layers and total corneal density were significantly higher in the POAG than the control group ( P <0.05). Total corneal density was positively correlated with age ( r =0.623; P <0.001) and also showed a good diagnostic capacity for glaucoma [area under the curve=0.617; 95% confidence interval (CI): 0.541-0.697; P <0.001]. In a multiple linear regression designed to assess its relationship with age, sex, central corneal thickness, and K mean, age emerged as a significant confounder both in controls (coefficient=0.315; P <0.001; 95% CI: 0.246-0.384) and patients (coefficient=0.370; P <0.001; 95% CI: 0.255-0.486). Conclusion: Corneal densitometry measurements showed a good diagnostic capacity for POAG suggesting this type of examination could have clinical applications in the diagnosis and management of glaucoma.